Association of Visceral Obesity-Related Indices With Coronary Collateralization in Patients With Chronic Total Occlusion - Shao, Meng-Jiao; Luo, Jun-yi; Shi, Jia; Liu, Fen; Shan, Chun-fang; Luo, Fan; Yu, Xiao-lin; Zhao, Qian; Tian, Ting; Li, Xiao-Mei; Yang, Yi-ning (Frontiers in Cardiovascular Medicine, 2021)
Background: Obesity is an independent risk factor for cardiovascular disease. We investigated whether and to what extent visceral obesity-related indices were associated with coronary collateralization (CC) in chronic total occlusion (CTO) patients. Methods: This retrospective cohort study involved 1,008 consecutive patients with CTO who underwent CTO-percutaneous coronary artery intervention (PCI). CC was graded according to the Rentrop scoring system. Data on demographic and clinical characteristics were collected by cardiovascular doctors. Logistic regression, receiver operating characteristic (ROC) curve and Kaplan-Meier analyses were performed to assess the predictive value of visceral obesity-related indices for CC. Results: Overall, 1,008 inpatients were assigned to the poor CC group (n = 592) and good CC group (n = 416). In multivariate-adjusted logistic regression analyses, all visceral obesity-related indices (P-value < 0.001) were significantly associated with CC. After ROC analysis and the Delong test, the Chinese visceral adiposity index (CVAI) had the largest area under the curve (AUC) of 0.741 (0.711–0.771). Further analysis revealed that CVAI quartile remained a risk factor for poor CC in all groups, CVAI was associated with a 1.018-fold higher risk of poor CC (OR = 1.018, 95% CI: 1.014–1.021, P < 0.001). Individuals in the top CVAI quartile group had the highest risk of poor CC (OR = 10.657, 95% CI: 6.492–17.493, P < 0.001). Subgroup analyses showed similar results, and CVAI quartile remained a risk factor for poor CC. Moreover, increased CVAI predicted poor prognosis in CTO patients. Conclusion: In summary, this study indicated that all the increased visceral obesity-related indices were significantly associated with increased poor CC risk. After adjusting for potential risks, CVAI had the best performance for estimating CC and predicting prognosis in CTO patients.